The Diversity of Mycorrhiza Arbuscular Fungi in Several Types of Peatland Utilization in Sungai Asam Village Kubu Raya District - Dwi - Zulfita; Agus Hariyanti; Surachman Surachman (JOURNAL OF TROPICAL SOILS, 2020)
The purpose of this study was to determine the diversity of FMA from the rhizosphere of cassava, corn, taro, ginger, kale, pineapple which was cultivated in the Sungai Asam peatland by using a corn plant host. This research was conducted at the Soil Biology and Biotechnology Laboratory of the Faculty of Agriculture and plastic houses in the Universitas Tanjungpura Faculty of Agriculture’s experimental garden. The study was conducted from August 2nd to October 21st, 2018. The procedure was done by taking soil and root samples from cassava, corn, taro, and peanut rhizosphere cultivated on peatland. A sampling of soil and roots in each rhizosphere was carried out at 4 observation points as replication with a depth of 0-20 cm and a diameter of 20 cm and then put into a plastic bag and labeled. Then, the soil samples taken were used for microscopic analysis (extraction and identification) and were analyzed to determine their chemical properties. Root samples were colorized to determine the percentage of colonization, and corns were used to cultivate. Furthermore, extraction and identification of spores were carried out using the same technique as extraction and identification of soil samples. The variables observed included the percentage of root colonization, spore density, and spore diversity. The FMA diversity of the 6 types of peatland utilization from the rhizosphere of cassava, corn, taro, ginger, pineapple, and kale in the Sungai Asam village before and after trapping showed an increase in the number of spores, diversity of FMA”while the percentage value of root colonization was varied. Moreover, the number of spores increased from around 36 - 52 spores per 50 g of soil to 61 - 178 spores per 50 g of soil. The diversity of spore types increased from 10 types of Glomus, 1 type of Gigaspora, and 4 types of Acaulospora to 13 types of Glomus, 3 types of Gigaspora, and 5 types of Acaulospora. The highest percentage of infected roots before trapping ranged from 48.89% - 78.48% and after trapping ranged from 78.89% - 94.80%.